Dielectric Properties of Y,Cu,Ti,0,, and Effect of Doping at its Different sites - Sharma, Mrs. Sunita (iit bhu varanasi, 2016)
Electronic industries are in constant search of high performance dielectric materials exhibiting temperature and frequency-stability, colossal permittivity (εr > 1000) and sufficiently low dielectric loss. It facilitates miniaturization of high-energy density storage devices such as Dynamic Random Access Memory (DRAM) devices, Multi Layer Ceramic Capacitors (MLCC) and many other electronic devices in automobile and aircraft. Traditional Pb(ZrxTi1-x)O3 and BaTiO3-based ferroelectric materials exhibit high dielectric properties. However, their dielectric properties are strongly temperature-dependent due to phase transition at Curie temperature (Tc). Furthermore, lead-based materials are eco-unfriendly and harmful to health. Hence, it is necessary to find some non-ferroelectric materials with high dielectric constant to substitute these traditional materials.
This thesis submitted by IIT BHU Varanasi, Phd scholar and supervised by Prof. K. D. Mandal and Prof. M. M. Singh.
Keywords: Dielectric Properties; Effect of Doping